2022
DOI: 10.1155/2022/8215348
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Esthetically Depigmented Gingiva in a Short Operative Duration, Using Two Modes of 940 nm Diode Lasers—A Randomized Clinical Trial

Abstract: Aim. This study aims to compare the effectiveness of the two modes of 940 nm diode lasers on gingival depigmentation. Methods. Twenty patients (11 females and 9 males) participated in this study; they were free of any systemic or local condition and randomly assembled into two groups: continuous wave (CW) and pulsed groups, in contact modes. The diode laser was of 940 nm wavelength and 1-2 W irradiation power for the two modes in all cases. A single session of irradiation was applied to the facial gingivae of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Moreover, it was shown that laser techniques associated with less postoperative complications such as pain, bleeding, discomfort, and infection when compared to conventional surgical techniques. 16 , 28 , 29 , 30 , 31 Also, it is required to apply periodontal pack after gingival depigmentation using conventional techniques, whereas, when using lasers, there is no need for it, because a white fibrin slough will appear in the first days following the procedure, which will serve as a biological wound dressing that seals the ends of sensory nerves. 32…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was shown that laser techniques associated with less postoperative complications such as pain, bleeding, discomfort, and infection when compared to conventional surgical techniques. 16 , 28 , 29 , 30 , 31 Also, it is required to apply periodontal pack after gingival depigmentation using conventional techniques, whereas, when using lasers, there is no need for it, because a white fibrin slough will appear in the first days following the procedure, which will serve as a biological wound dressing that seals the ends of sensory nerves. 32…”
Section: Discussionmentioning
confidence: 99%